The Great Introduction to Astrology by Abū Maʿšar (2 volumes) - Yamamoto, Keiji. (Islamic Philosophy, Theology and Science. Texts and Studies, 2018)
Abū Ma'͑šar's Great Introduction to Astrology (mid-ninth century) is the most comprehensive and influential text on astrology in the Middle Ages. In addition to presenting astrological doctrine, it provides a detailed justification for the validity of astrology and establishes its basis within the natural sciences of the philosophers. These two volumes provide a critical edition of the Arabic text; a facing English translation, which includes references to the divergences in the twelfth-century Latin translations of John of Seville and Hermann of Carinthia (Volume 1); and the large fragment of a Greek translation (edited by David Pingree). Comprehensive Arabic, English, Greek and Latin glossaries enable one to trace changes in vocabulary and terminology as the text passed from one culture to another. (Volume 2.)